AUDIENCE RECEPTION ANALYSIS OF THE SMOKING BAN CASE AT SMAN 1 CIMARGA IN @BANGSAONLINE TIKTOK CONTENT - Robbikal Muntaha Meliala; Indria Kumala (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
In the digital era, communication technology has brought about significant changes in the dissemination of information through the phenomenon of virality on social media. TikTok has become one of the main platforms used by the public to quickly access information, including news content about cases in educational institutions. One case that attracted public attention was a post by the TikTok account @bangsaonline regarding a smoking ban for students that resulted in physical action by the Principal of SMAN 1 Cimarga. The researcher chose this content because it sparked widespread debate and created a domino effect that could potentially influence public perception of the image of education. The purpose of this study was to determine how the audience reception analysis of the smoking ban case for students of SMAN 1 Cimarga in the TikTok news content @bangsaonline. This study used a qualitative method with a netnography approach and Stuart Hall's reception analysis theory. The results showed that informants interpreted the message differently based on their backgrounds and personal experiences. No informants were found in the opposition position, but the majority were in the negotiation position (8 people) and the dominant hegemonic position (2 people). This indicates that although the audience accepted the smoking ban message, they remained critical and negotiated the disciplinary method implemented by the Principal.